Detection of laryngeal function using speech and electroglottographic data - Childers, D.G.; Bae, K.S. (IEEE transactions on biomedical engineering, 1992)
The purpose of this research was to develop quantitative measures for the assessment of laryngeal function using speech and electroglottographic (EGG) data. Two procedures for the detection of laryngeal pathology were developed: (1) a spectral distortion measure using pitch synchronous and asynchronous methods with linear predictive coding (LPC) vectors and vector quantization (VQ), and (2) analysis of the EGG signal using time interval and amplitude difference measures. The VQ procedure was conjectured to offer the possibility of circumventing the need to estimate the glottal volume velocity waveform by inverse filtering techniques. The EGG procedure was to evaluate data that was 'nearly' a direct measure of vocal fold vibratory motion and thus was conjectured to offer the potential for providing an excellent assessment of laryngeal function. A threshold based procedure gave 75.9 and 69.0% probability of pathological detection using procedures (1) and (2), respectively, for 29 patients with pathological voices and 52 normal subjects. The false alarm probability was 9.6% for the normal subjects.< >